2014
DOI: 10.1007/s00418-014-1189-y
|View full text |Cite
|
Sign up to set email alerts
|

Electron tomography and cryo-SEM characterization reveals novel ultrastructural features of host-parasite interaction during Chlamydia abortus infection

Abstract: Chlamydia (C.) abortus is a widely spread pathogen among ruminants that can be transmitted to women during pregnancy leading to severe systemic infection with consecutive abortion. As a member of the Chlamydiaceae, C. abortus shares the characteristic feature of an obligate intracellular biphasic developmental cycle with two morphological forms including elementary bodies (EBs) and reticulate bodies (RBs). In contrast to other chlamydial species, C. abortus ultrastructure has not been investigated yet. To do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Conversely, ECT also revealed the adaptations that accompany the differentiation of C. trachomatis from reticulate bodies into elementary bodies, such as a near doubling in the thickness of the outer membrane 142 . ECT of another pathogen, Chlamydophila abortus , showed that it has a similar T3SS structure and differentiation strategy to C. trachomatis 143 . ECT also identified that a previously identified Chlamydial development stage, the crescent-shaped stage, was actually an artefact of the chemical fixation and dehydration used in traditional electron microscopy preparations 6 , highlighting the power of ECT to image native structures.…”
Section: Pathogenicitymentioning
confidence: 99%
“…Conversely, ECT also revealed the adaptations that accompany the differentiation of C. trachomatis from reticulate bodies into elementary bodies, such as a near doubling in the thickness of the outer membrane 142 . ECT of another pathogen, Chlamydophila abortus , showed that it has a similar T3SS structure and differentiation strategy to C. trachomatis 143 . ECT also identified that a previously identified Chlamydial development stage, the crescent-shaped stage, was actually an artefact of the chemical fixation and dehydration used in traditional electron microscopy preparations 6 , highlighting the power of ECT to image native structures.…”
Section: Pathogenicitymentioning
confidence: 99%
“…High pressure freezing, freeze substitution, and embedding were performed as previously described ( Wilkat et al, 2014 ) with minor changes. Freeze substitution was performed for London Resin gold embedding.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded on pretreated sapphire disks [32] and cultivated for 48h before high-pressure freezing was performed according to Walther et al [33]. Freeze-substitution was performed in medium consisting of acetone (VWR International GmbH, Darmstadt, Germany) with 0.1% uranyl acetate (Merck KGaA, Darmstadt, Germany) and 5% water [34].…”
Section: Methodsmentioning
confidence: 99%
“…Freeze-substitution was performed in medium consisting of acetone (VWR International GmbH, Darmstadt, Germany) with 0.1% uranyl acetate (Merck KGaA, Darmstadt, Germany) and 5% water [34]. Afterwards, cells were embedded in LR-Gold and cut according to Wilkat et al, 2014 [32]. For immunogold staining ultrathin sections were first incubated in 1% BSA for 10min and subsequently in ms α APP/Aβ-antibody (6E10) diluted 1:50 in 1% BSA blocking solution for 30min.…”
Section: Methodsmentioning
confidence: 99%